If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4t+-36+6t=3t
We move all terms to the left:
-4t+-36+6t-(3t)=0
We add all the numbers together, and all the variables
-t=0
t=0/-1
t=0
| (2c-1)^2=25 | | 11z=8 | | 4(3y+4)=10 | | 9x+7=25+2(5-x) | | -11/3m+1/6m=-7 | | (2c-1)^2-4=21 | | -6(4-v)=-24+6v | | (x-3/4)=2/3(3/2x-9/14) | | 2p/2=14 | | 2v+11=29-v | | 16-(11/5y)-y=0 | | 13r-3=3r+87 | | 10=4^x/5 | | 5x×4=24 | | 3z=z+4 | | 2k+20=13k-13 | | 15x-10x=x-12 | | 1.6x-7.3=9.6-2.3x | | -6(x-15)=-84 | | r/2-6=-4 | | 4-5n=99 | | 20=-u/9 | | 5u-17=8 | | 11x+17=x+67 | | 2x+5=8x12= | | 3/10=57.75/x | | 30/100=57.75/x | | 175m-125m+42,750=45,900-175m | | X^2-3x+2.25=1.25 | | 4.1g+9=1.1g+24 | | 10(1.8-0.6y)+6y=18 | | 3/7a+2/3=7/9 |